2009
DOI: 10.1111/j.1440-1681.2009.05241.x
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin gene‐related peptides: Multifunctional endocrine / autocrine modulators in health and disease

Abstract: 1. Ghrelin is a multifunctional peptide hormone that affects various processes, including growth hormone and insulin release, appetite regulation, gut motility, metabolism and cancer cell proliferation. Ghrelin is produced in the stomach and in other normal and pathological cell types. It may act as an endocrine or autocrine/paracrine factor. 2. The present article reviews recent findings in the study of ghrelin and its receptor that suggest that the ghrelin gene locus may give rise to a number of functional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 85 publications
(188 reference statements)
1
23
1
Order By: Relevance
“…The differences between ghrelin and obestatin immunoreactivity in benign and malignant thyroid tumors could support the theory of alternative transcription of pre-proghrelin gene and thus of independent production of ghrelin and obestatin [38]. In this study there was no correlation between ghrelin and obestatin immunoreactivity in any of the analyzed groups.…”
Section: Discussioncontrasting
confidence: 36%
“…The differences between ghrelin and obestatin immunoreactivity in benign and malignant thyroid tumors could support the theory of alternative transcription of pre-proghrelin gene and thus of independent production of ghrelin and obestatin [38]. In this study there was no correlation between ghrelin and obestatin immunoreactivity in any of the analyzed groups.…”
Section: Discussioncontrasting
confidence: 36%
“…Then, the proghrelin undergoes proteolytic process which results in the mature ghrelin (28 AA) and the C-terminal propeptide C-ghrelin (66 remaining AA) production. C-ghrelin may be further cleaved to discharge obestatin (23AA) and/or other peptides (Pemberton et al 2008, Seim et al 2010.…”
Section: Ghrelin Is Not Only One Peptidementioning
confidence: 99%
“…From the same gene of ghrelin, through a posttranslational or an alternative splicing process, a peptide named obestatin is obtained [3,9]. This is a 23 amino acid amidated peptide identical to residues 76-98 of the C-terminal peptide of preproghrelin, also isolated in the rat stomach [9].…”
Section: Obestatinmentioning
confidence: 99%
“…Another reason for the metabolic discrepancies can be related to the peculiar U-shape of the dose response curve [57]. The opposing effects of obestatin and ghrelin are controversial and some authors suggest that obestatin could act as a paracrine/autocrine factor, being degradated rapidly in the serum [62].Some studies have demonstrated that obestatin stimulates cell proliferation in prostate cancer cells, ovarian cancer cells [3], gastric cancer cells [63] and ovarian granulosa cells [64]. Obestatin has also been reported to regulate sleep [65], to affect memory and anxiety [66], and to inhibit thirst [67].…”
mentioning
confidence: 99%
See 1 more Smart Citation